The Effect of Organic Diluent on the Extraction of Eu(III) by HEH[EHP]. Issue 3 (7th June 2019) - Lécrivain, Thibaut; Kimberlin, Ashleigh; E. Dodd, Devon; Miller, Samuel; Hobbs, Ian; Campbell, Emily; Heller, Forrest; Lapka, Joseph; Huber, Matthew; Nash, Kenneth L.
ABSTRACT: Because there are fewer tools available to probe the interactions therein, the effect of the fundamental chemistry of the organic diluent on solvent extraction equilibria has been under-characterized relative to the aqueous. As a result, diluents for solvent extraction are often selected for an application not for their utility as a medium for reaction, but for other (often equally) important reasons (like low flammability). To begin to improve this imbalance in the science, twenty different diluents have been used in a study of the extraction of radiotracer 152/154 Eu 3+ from dilute nitric acid solutions using the extractant 2-ethylhexylphosphonic acid mono-2-ethylhexyl ester (HEH[EHP]). To increase the utility of the study and to honor the memory of Professor Jan Rydberg, this investigation was conducted by a cadre of comparatively inexperienced separation scientists (who are as a result no longer inexperienced separation scientists) as a radioanalytical chemistry and solvent extraction educational exercise. Slope analysis was used to determine the apparent stoichiometry of the extracted metal complex. The results discussed in the following indicate that, while the pH dependence exhibits the expected three H + exchanged per metal ion extracted, the extractant dependence suggests that the number of protonated extractant molecules in the extracted complex changes with the organic diluent. The experimentally observed "extractant dependency" ranges from 2.5 to 3.0 dimer equivalent molecules per extracted metal ion. Ironically, in the diluents exhibiting the highest apparent M:(HA)3 stoichiometry, HEH[EHP] extracts Eu 3+ less efficiently. Europium luminescence spectroscopy was used to probe for changes in the first coordination sphere of the complex in different diluents. A model and conceptual framework for understanding these observations is described.